Design and development of sedimentation measurement device for magnetorheological fluid - Faris Imadi, Ahmad Nadzri (2016)
The measurement of particles sedimentation in the magnetorheological fluid (MRF) can be performed by the method of visual inspection, digital photography and electromagnetic induction. However, the visual inspection method produces poor accuracy result due to the observer’s parallax error. While the digital photography method requires proper lighting in order to obtain good image before it can be processed. For electromagnetic induction method, the sedimentation measurement only can be performed to particles that have good magnetic permeability. To overcomes these drawbacks, laser light transmission may become the alternative method for measuring the particle sedimentation. This thesis discusses about design and development of a sedimentation measurement device for MRF based on laser light transmission. The objectives of the work are to design and fabricate a prototype of settling monitoring device based on light transmission by using a laser diode as light source and a photodiode as photodetector, to verify the reliability of the light transmission-receiving system of the prototype by using ultraviolet–visible (UV-Vis) spectrophotometer, and to evaluate the prototype by measuring the sedimentation rate of iron particles in three MRF types with different composition. The sedimentation measurement device was designed and developed. For the light transmission-receiving system, a laser diode (650 nm) was used as light transmitter and a photodiode was used as light receiver. The reliability of this system was evaluated by locating the wavelength that give the highest particles detection at clear part of three different MRF samples. The result for this experiment suggest that the wavelength ranging from 411 nm to 421 nm give the highest level of the particles detection. Besides that, the comparison between the light absorbance of the clear parts of the three samples measured by UV-Vis spectrophotometer and measured by the developed device was carried out. The outcome from the comparison shows that the light detector used in the prototype could not give the same detection sensitivity as the light detector of the UV-Vis spectrophotometer due to the mismatch between the laser wavelength and the photodiode peak sensitivity wavelength. In addition, the developed device also was evaluated by conducting the sedimentation analysis for three different compositions of MRF samples. The evaluation result presents that the prototype was able to perform the sedimentation monitoring for the samples examined.